NEXUS Gains Talk 8: A Nexus Agreement on Biodiversity: 23 Global Targets for Nature and People - DeClerck, Fabrice A.J.; Navarrete Frias, Carolina (CGIAR System Organization, 2023)
This seminar explores the outcomes of the 15th meeting of the Conference of the Parties to the UN Convention on Biological Diversity (CBD COP15) from a systems perspective, and discusses the implications and opportunities for research and development.